2005
DOI: 10.1159/000085921
|View full text |Cite
|
Sign up to set email alerts
|

Urothelial Cancer of the Renal Pelvis in Percutaneous Nephrolithotomy Patients

Abstract: Introduction: The association between staghorn calculus of the kidney long-standing and urothelial tumors of the renal pelvis is well documented. We describe 3 patients with urothelial cancer in a kidney who underwent percutaneous nephrolithotomy (PCNL). Patients and Methods: Retrospective analysis of our series of more than 500 PCNLs revealed 3 patients in whom urothelial cancer of the renal pelvis was diagnosed during or following percutaneous stone removal. Preoperative assessment included IVP, renal sonogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 18 publications
(28 reference statements)
1
15
0
2
Order By: Relevance
“…In addition, studies in the relevant literature report that malakoplakia, which is a chronic inflammatory disease of unknown etiology, may be accompanied by malignant tumors. [1][2][3] plasms can develop in longstanding non-functioning nephrolithic kidneys and clinical approach should be applied accordingly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies in the relevant literature report that malakoplakia, which is a chronic inflammatory disease of unknown etiology, may be accompanied by malignant tumors. [1][2][3] plasms can develop in longstanding non-functioning nephrolithic kidneys and clinical approach should be applied accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…Kidneys in this condition fail to function properly and there is also a high risk of developing urothelial neoplasm. [1][2][3] We report on a case of concurrent urothelial carcinoma and malakoplakia in a non-functioning nephrolithic kidney.…”
Section: Introductionmentioning
confidence: 99%
“…Th e association of TCC, small cell carcinoma, adenocarcinoma and sarcomatoid carcinoma with renal stone disease has been documented in the literature [18][19][20] . Urothelial cancer of the renal pelvis in patients undergoing PCNL was studied previously.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only one study related to the incidental diagnosis of urothelial malignancy during PCNL has been published -a study based on the records of 500 patients who underwent PCNL for renal stones [18] . In that study, 1 patient was diagnosed postoperatively after CT revealed a renal lesion, 1 patient underwent simple nephrectomy due to a non-functioning kidney and the tumor was found due to pathological analysis, and 1 patient had suspicious findings in the renal pelvis during PCNL and subsequent pathological examination of the renal pelvis biopsies revealed TCC with sarcomatoid features.…”
Section: Discussionmentioning
confidence: 99%